2017
DOI: 10.1038/mi.2016.106
|View full text |Cite|
|
Sign up to set email alerts
|

Broadly neutralizing antibodies suppress post-transcytosis HIV-1 infectivity

Abstract: Broadly neutralizing antibodies (bNAbs) offer promising opportunities for preventing HIV-1 infection in humans. Immunoprophylaxis with potent bNAbs efficiently protects non-human primates from mucosal transmission even after repeated challenges. However, the precise mechanisms of bNAb-mediated viral inhibition in mucosal tissues are currently unknown. Here, we show that immunoglobulin (Ig)G and IgA bNAbs do not interfere with the endocytic transport of HIV-1 across epithelial cells, a process referred to as tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 85 publications
(125 reference statements)
3
16
0
Order By: Relevance
“…The isolated high-affinity gp140 antibodies targeted mainly gp41 and lacked neutralizing activity, potent ADCC breadth, and blocking capacity against HIV-1 transcytosis. In contrast to HIV-1 bNAbs ( Lorin et al., 2017 ), mucosal HIV-1 nnAbs did not suppress post-transcytosis infectivity in vitro . Although HIV-1 nnAbs may modestly diminish the number of transmitted viruses ( Santra et al., 2015 ), recent reports demonstrated that viral neutralization is required to confer protection against mucosal HIV-1 transmission in vitro and in vivo ( Astronomo et al., 2016 , Cheeseman et al., 2016 ).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The isolated high-affinity gp140 antibodies targeted mainly gp41 and lacked neutralizing activity, potent ADCC breadth, and blocking capacity against HIV-1 transcytosis. In contrast to HIV-1 bNAbs ( Lorin et al., 2017 ), mucosal HIV-1 nnAbs did not suppress post-transcytosis infectivity in vitro . Although HIV-1 nnAbs may modestly diminish the number of transmitted viruses ( Santra et al., 2015 ), recent reports demonstrated that viral neutralization is required to confer protection against mucosal HIV-1 transmission in vitro and in vivo ( Astronomo et al., 2016 , Cheeseman et al., 2016 ).…”
Section: Discussionmentioning
confidence: 65%
“…Transcytosis assays were performed using epithelial monolayer-forming human endometrial carcinoma type A HEC-1A cells (ATCC ® HTB-112) cultivated on 0.4 μm polyethylene terephthalate transwell membranes (Millicell ® , Millipore) as recently described ( Lorin et al., 2017 ). Briefly, the confluence, tightness and integrity of HEC-1A monolayers were controlled by measuring the transepithelial electrical resistance, the paracellular permeability to 40 kDa FITC-labeled DEAE-dextran (Molecular Probes) and by assaying the expression of tight junction proteins by confocal microscopy as previously described ( Lorin et al., 2017 ). HIV-1 viruses (10 ng of p24 HIV-1 NLAD8) were incubated v/v for 1 h at 37°C with purified antibodies (66.67 nM final concentration), and mixtures were added onto HEC-1A monolayers at day 6 of culture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody binding to viruses on infected cells was assayed by flow cytometry as recently described ( Bruel et al., 2016 ). Neutralization of cell-free HIV-1 was measured using TZM-bl cells as previously described ( Li et al., 2005 , Lorin et al., 2017 ). To assay for CHIKV neutralization, luciferase-based and plaque neutralization assays were used, as described in the Supplemental Experimental Procedures .…”
Section: Methodsmentioning
confidence: 99%
“…The reason for this discrepancy is unknown but may be related to the utilization of older-generation or less potent bNAbs in the prior studies (2F5, 2G12, 4E10), whereas the most recent studies investigate newer-generation, more potent bNAbs. In that study of bNAbs targeting a wide range of epitopes, bNAbs did not block the transcytosis of either cell-free or cell-associated HIV-1 in vitro and instead relied upon neutralization to decrease the infectivity of transcytosed viruses ( 105 ). Thus, increasing the local concentration and neutralization breadth and potency of bNAbs at mucosal sites may enhance protection against mucosal infection.…”
Section: Enhancing Preexposure Prophylactic Potential: Preventing Virmentioning
confidence: 99%